Ethical Issues of Health Technology Co-Creation - Collanus Eva; Kielo-Viljamaa Emilia; Lahtiranta Janne; Tuomisto Antti (Germany, 2022)
In healthcare, co-creation has become the de facto method for creating new products and services. In practice, every major city in Finland offers services where new products can be created together with the domain specialists and endusers. While co-creations as an ideal, fits to the Scandinavian mindset of lowthreshold co-operation where everyone can participate regardless of the “file and rank”, there are – primarily ethical – issues that need to be taken into consideration. More so when the approach is applied to the field of healthcare where moral values, such as benevolence and beneficence, typically supersede the more business-oriented ones. In this article, we identify some of these challenges and discuss their implications from different practical perspectives: who should take part in co-creation and why, who can represent the whole group, what should be taking into consideration when deciding co-creation communication methods, and who is responsible if co-creation processes fail.
Proceedings of the Conference on Technology Ethics Turku, Finland, October, 20-22, 2021